Chemical Insights into the Anchinopeptolide Series. Issue 31 (14th June 2019) - Bastos Lemos Silva, Siguara; Beniddir, Mehdi A.; Gallard, Jean‐François; Poupon, Erwan; Thomas, Olivier P.; Evanno, Laurent
Abstract : The chemical composition of the marine sponge Phorbas tenacior was investigated in depth. The anchinopeptolides A–D bearing a central pyrrolidinone were isolated together with a new congener named anchinopeptolide E corresponding to an epimer of anchinopeptolide C. The relative configuration of the central core of anchinopeptolide E was determined by extensive NMR analyses. Additionally, the previously isolated cyclobutane derivative cycloanchinopeptolide C was not detected from the sponge extract but could be synthesised by a photoinduced intramolecular [2+2] cycloaddition giving convincing evidence for its artefactual origin. Abstract : The chemical composition of the marine sponge Phorbas tenacior was investigated in depth. The anchinopeptolides A–D bearing a central pyrrolidinone were isolated together with a new congener named anchinopeptolide E. Cyclobutane derivative cycloanchinopeptolide C was not detected from the sponge extract but could be synthesised by a photoinduced intramolecular [2+2] cycloaddition giving convincing evidence for its artefactual origin.